Modificación de la textura de alimentos para los adultos mayores - Wendy J. Dahl (EDIS)
This 2-page Spanish-language fact sheet discusses information on altering food texture for older adults and offers tips for enhancing puréed and ground foods. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, May 2011.